Anal Sphincteroplasty and Counter-Clockwise Gracilis Muscle Transposition by Using Transperineal Ischioanal Fossa Access in a Male Patient with Fecal Incontinence Who Undergone to Low Anterior Resection for Rectal Cancer - Ali Naki Yücesoy; Mehmet Çağlıkülekçi; Emre Sivrikoz (Turkish Journal of Colorectal Disease, 2018)
Fecal incontinence is a clinical condition that negatively affects the patient’s social and psychological life, and presents a surgical challenge due to dissatisfactory postoperative outcomes. Here we discuss the case of a 72-year-old male patient who underwent intersphincteric low anterior rectal resection for low rectal cancer one year earlier and developed complete fecal incontinence. We achieved good postoperative results in this patient by performing transperineal anal sphincteroplasty and counter-clockwise gracilis muscle transposition.